Descriptions of three new species of the harvestmen genus Pseudogagrella (Opiliones: Sclerosomatidae: Gagrellinae) from Taiwan, supported by morphological and molecular evidence - Chen, Ssu-Li; Shih, Hsi-Te (Zootaxa, 2017)
Three new species of Opiliones are delimited and described from central and northern Taiwan based on morphological and molecular evidence. Pseudogagrella dorsomaculata sp. nov., collected from the Dasyueshan Forest Recreation Area, Heping, Taichung, resembles P. andoi Suzuki 1977, but can be recognized by the different pattern of the first abdominal tergite and the morphology of the penile grans. Pseudogagrella nigridorsa sp. nov., collected from the Lalashan National Forest Sanctuary, Fusing, Taoyuan, resembles P. arishana Suzuki 1977, but can be recognized by the different pattern of legs and the morphology of the penile stylus. Pseudogagrella sauteri sp. nov., also collected from the Dasyueshan Forest Recreation Area, resembles P. cyanea (Roewer 1915) and P. taiwana Suzuki 1977, but can be distinguished by the morphology of the alate part of the penis. Molecular evidence from mitochondrial 16S rDNA and cytochrome oxidase subunit I (COI) supports the identity of the three new species.